Moshpit Medicine: The Experience of an Australian Event Resuscitation Team. Issue 3 (4th June 2020) - Wing, Sean; Johnson, Robert; Fowler, Leigh
Abstract: The authors reviewed case reports of patients presenting to an advanced medical assessment and resuscitation service at 15 music events over 22 days from June 2018 through March 2019 around Australia. Event size ranged from 4, 000 to 57, 500 participants. Events observed had a mean patient presentation rate (PPR) of 0.83% (SD = 0.59%) and mean transport to hospital rate (TTHR) of 1.89 (SD = 0.92) per 10, 000. Two-hundred and twenty-one cases were reviewed and tabulated for descriptive analysis. Lower rates of traumatic injuries were seen compared to other case reports, and minor procedures represented a minor but important part of the team's workload. Methylenedioxymethamphetamine (MDMA) use was reported by 33.0% of patients on the day of presentation; almost one-half of these reported a co-ingestion. Patients presenting after using MDMA were more likely to have an elevated temperature. Eight percent of patients presented with temperature above 38°C. Patients with an initial temperature above 38°C were more likely to require hospitalization. On-site electrocardiograph (ECG), blood gas, ultrasound, and urinalysis were found to be useful in decision support. In total, 29.8% of patients required sedation during their encounter; 2.7% required rapid sequence induction at the event. Mean observation time was 44 minutes, with longer observation required in MDMA and hallucinogen-related presentations.